PATTERNS OF LINEAR CORRESPONDENCE IN THE GOTHIC BIBLE TRANSLATION: THE CASE OF THE ADJECTIVE - Ratkus, Artūras (Vertimo studijos, 2017)
By examining the realisation of the adjective in Gothic against the original Greek, this paper explores the borderline between literalness and idiomaticity in the Gothic translation of the Bible. As a general rule, the Gothic translation follows the linearity of the Greek model very closely. Occasionally, however, Gothic strays from the Greek, the most typical types of deviation being concerned with the use of different grammatical material, function and word order. Where Gothic innovates elements unattested in the original or deviates in word order, it likely asserts its native properties. It is argued that, as a whole, the Gothic text presents in itself a mixture of truly idiomatic and marginally acceptable language.